2002
DOI: 10.1063/1.1430024
|View full text |Cite
|
Sign up to set email alerts
|

n- GaN surface treatments for metal contacts studied via x-ray photoemission spectroscopy

Abstract: The surface chemistry and electronic properties of n-GaN surfaces were studied via x-ray photoemission spectroscopy before and after wet chemical treatments. Shifts of the surface Fermi level were measured with the change in position of the Ga 3d core level peak. HCl treatment of n-GaN led to a 0.9 eV shift of the surface Fermi level toward the conduction band minimum, while KOH treatment led to a 0.3 eV shift of the surface Fermi level toward the valance band maximum. These shifts lead to a reduction in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 18 publications
6
43
0
Order By: Relevance
“…These effects could be due to a surface photovoltage effect or to a resistive voltage drop at the contacts of the sample and at the depletion region below the surface 25 and are mentioned in Ref. 4. These effects lead to a change in the band bending and can complicate the measurement of the surface-barrier height as previously observed during the investigation of Au deposition on GaN via photoemission.…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…These effects could be due to a surface photovoltage effect or to a resistive voltage drop at the contacts of the sample and at the depletion region below the surface 25 and are mentioned in Ref. 4. These effects lead to a change in the band bending and can complicate the measurement of the surface-barrier height as previously observed during the investigation of Au deposition on GaN via photoemission.…”
Section: Methodsmentioning
confidence: 88%
“…For n-GaN, HCl has been shown previously to decrease the surface-barrier height presumably through creation of N vacancies that pin E F close to the conduction-band minimum ͑CBM͒. 4 For aqua regia treatment of p-GaN, it has been shown that E F pins near the valence-band maximum ͑VBM͒, coincident with the Ga vacancy states, decreasing the surface-barrier height. 7 Al and Ti may be expected to behave similarly, since both are strong nitride formers ͑AlN and TiN͒.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it appears that in addition to a surface dipole, the HCl process must modify the band bending at the N-face surface. 14 Considering all of the results here, the band bending at the as-received N-face surface is initially flat or slightly upward and increases as a result of the HCl clean. The deduced net charge is not large enough to account for the observed change in surface potential.…”
mentioning
confidence: 99%